2019
DOI: 10.4236/fns.2019.105040
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Some Flavor Components, Microbiological and Microstructure Characteristics of Corn Milk Yoghurt

Abstract: Corn milk is considered as a new innovation especially in the making of yoghurt based products. The present study was conducted to study antioxidants components such as (phenols compounds and DPPH scavenging activity), total volatile free fatty acids, microbiological and microstructure characteristics in yoghurt samples produced from two different ratios of buffalos and corn milk (70:30 coded A and 60:40 coded B) respectively. Results indicated that the increasing ratio of corn milk led to increase the content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…However, the addition of corn milk of up to 20-30% can be used to manufacture soft cheese, which the consumers have accepted. This finding agrees with Ibrahim et al (2019) and Ateteallah and Osman (2019), who reported that corn milk could be incorporated with buffalo or cow milk to manufacture some dairy products.…”
Section: Sensory Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…However, the addition of corn milk of up to 20-30% can be used to manufacture soft cheese, which the consumers have accepted. This finding agrees with Ibrahim et al (2019) and Ateteallah and Osman (2019), who reported that corn milk could be incorporated with buffalo or cow milk to manufacture some dairy products.…”
Section: Sensory Propertiessupporting
confidence: 92%
“…The data show that the addition of corn milk significantly increased the DPPH radical scavenging ability ( p < 0.05), but the ratio of 60% cow milk to 40% corn milk treatment exhibited the highest radical scavenging ability with a value of 9.49 IC50 and, as previously stated, was also the most significant contributor of total phenolic. The high content of phenolic compounds present in corn milk is related to their antioxidant activity, which provides beneficial health effects, such as the prevention of cancerous diseases (Ateteallah & Osman, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A young corn, one of the types of sweet corn that people like the most, is usually consumed by the community in processed products such as boiled corn or roasted corn. Sweet corn is confirmed in its antioxidant content [16]. Sweet corn is one of food commodities which has a bright future since its superiority on sweet taste, soft texture, and high demand on the market.…”
Section: Introductionmentioning
confidence: 99%